Analysis of Students Interests, Motivations, and Obstacles to Online Learning During the Covid-19 Pandemic - Salmawati, Salmawati; Halim, Abdul; Yusrizal, Yusrizal; Halim, Lilia (Universitas Syiah Kuala, 2021)
This study raises the issue of how and whether there are differences in students' interests, motivations, and barriers to online learning during the covid-19 pandemic in Rikit Gaib High School Student and Pantan Cuaca High School Student. This study aims to find out how and whether there are differences in students' interests, motivations, and barriers to online learning during the covid-19 pandemic in Rikit Gaib High School Student and Pantan Cuaca High School Student. The benefits of this reearch are expected to provide secientific treasures and literacy in the field of education, epecially during this covid-19 pandemic mass and practical benefits for teacher to be able to find out how the minimum, student motivation and what are the learning obstacles during the covid-19 pandemi and students participate actively in the learning process.The subjects in this study were students Rikit Gaib High School Student and Rikit Gaib High School Student Pantan Cuaca of 50 people. The research approach used is descriptive qualitative. Data collection was carried out using a direct-based closed questionnaire. The data analysis technique used in this study is the percentage. Research result shows that the most dominant indicator of interest in learning is a sense of interest in online Rikit Gaib High School Student, less than half of students are interested in online learning, the most dominan indicator of learning motivasion is diligent in studying for High School Student Rikit Gaib more than half of students are diligent in learning online, and High School Student In Pantan Cuaca more than half students are diligent in learning online, And the most dominan indicator of learning obstacles is not being able to study properly in high school students Rikit Gaib more than half of the students can study properly and less than half of the students of High School Students Pantan Cuaca can study properly.